MODELLING HOME EQUITY CONVERSION LOANS WITH LIFE INSURANCE MODELS - Baškot, Bojan (Economic Annals, 2013)
Home equity represents a reserve that can be used for providing additional money for its owners during their retirement. Life insurance models can be successfully applied to model home equity conversion loans. The home equity conversion loan is a financial product that provides a certain flexibility by using home equity as a resource for a quality life during retirement. Home equity conversion loans do not have a predetermined maturity date, as do conventional loans. But, like every loan, it must be repaid. One potential advantage of using a home equity conversion loan during tough financial times instead of some types of need-based assistance is that eligibility is straightforward. Home equity conversion loans can be useful tools in the process of pension system reform.